Always the Backbone, Rarely the Leader: Black Women Activists and the Reconceptualization of Respectability during the 1960 Nashville Sit-in Movement - Amanda Hughett (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
In 1960 Nashville, change came from an unexpected place. Black college women renounced the protective environment of their campuses to participate in, and often lead, civil rights demonstrations alongside their black brothers. Yet, these black women’s valiant actions were not initially met with praise and gratitude from the city’s black community, who feared the women’s new radical behaviors transgressed the gendered boundaries of middle class respectability. Supportive male leaders claimed these young women’s actions were simply extensions of traditionally respectable black female attributes. Through the framework established by supportive male leaders, black college women continued to challenge and succeeded in shifting women’s respectable role in racial uplift work from that of invisible supporter to public leader, all the while maintaining the black community’s support — and admiration.
Keywords: Undergraduate Research; Pursuit